Trajectories of Emotional Exhaustion and Their Contribution to Depression: Optimism as a Buffer in Young People - Martha Cruz-Soto; Emmanuel Said Baeza-Torres; Luis Castañeda Pelaez; Jesús Rojas Jaimes; Jorge Palacios-Delgado (Brain Sciences)
Background: In Mexico, depression is one of the main mental health problems, with university students being particularly susceptible. Recent studies have explored the relationship between emotional factors and depression in young people. Our study investigates whether optimism buffers the indirect relationship between burnout, stress and coping in mitigating the negative effects on depressive symptoms in young university students. We hypothesized that optimism would moderate the negative impacts of stress and emotional exhaustion on depression. Methods: In total, 497 students of a university in Mexico participated (63% female and 36.6% male), ranging in age from 18 to 29. Students completed screenings for depression, emotional scales and optimism measures. Results: Emotional exhaustion and stress are direct predictors of depression. Although coping strategies did not have a direct effect, optimism mediated the relationship between stress and depression. Conclusions: These findings suggest that promoting optimism in university students could be an effective strategy to reduce depressive symptoms, especially in the context of socioemotional vulnerability.